Coronary artery Calcium predicts Cardiovascular events in participants with a low lifetime risk of Cardiovascular disease: The Multi-Ethnic Study of Atherosclerosis (MESA). (March 2016) - Joshi, Parag H.; Patel, Birju; Blaha, Michael J.; Berry, Jarett D.; Blankstein, Ron; Budoff, Matthew J.; Wong, Nathan; Agatston, Arthur; Blumenthal, Roger S.; Nasir, Khurram
Abstract: Aims: Patients with a low lifetime risk of coronary heart disease (CHD) are not completely free of events over 10 years. We evaluated predictors for CHD among "low lifetime risk" participants in the population-based Multi-Ethnic Study of Atherosclerosis (MESA). Methods: MESA enrolled 6814 men and women aged 45–84 years who were free of baseline cardiovascular disease. Using established criteria of non-diabetic, non-smokers with total cholesterol ≤200 mg/dL, systolic BP ≤ 139 mmHg, and diastolic BP ≤ 89 mmHg at baseline, we identified 1391 participants with a low lifetime risk for cardiovascular disease. Baseline covariates were age, gender, ethnicity, HDL-C, C-reactive protein, family history of CHD, carotid intima-media thickness and coronary artery calcium (CAC). We calculated event rates and the number needed to scan (NNS) to identify one participant with CAC>0 and > 100. Results: Over 10.4 years median follow-up, there were 33 events (2.4%) in participants with low lifetime risk. There were 479 participants (34%) with CAC>0 including 183 (13%) with CAC>100. CAC was present in 25 (76%) participants who experienced an event. In multivariable analyses, only CAC>100 remained predictive of CHD (HR 4.6; 95% CI: 1.6–13.6; p = 0.005). The event rates for CAC = 0, CAC>0 and CAC>100 were 0.9/1, 000, 5.7/1, 000, and 11.0/1000 person-years, respectively. The NNS to identify one participant with CAC>0 and > 100 were 3 and 7.6, respectively. Conclusions: While 10-year event rates were low in those with low lifetime risk, CAC was the strongest predictor of incident CHD. Identification of individuals with CAC = 0 and CAC>100 carries significant potential therapeutic implications. Highlights: Individuals with a low lifetime risk for cardiovascular disease (CVD) have a low burden of traditional risk factors. Despite this low lifetime risk, there are still CVD events over 10 year follow-up. High amounts of coronary artery calcification (CAC) was the only predictor of CVD among a low lifetime risk population. Those without CAC had the lowest absolute event rates. The utility of CAC testing across the CVD risk spectrum warrants more attention.